The Fragmentation of Style in Ann Beattie's Picturing Will - Gairaud Ruiz, Hilda (Universidad de Costa Rica. Campus Rodrigo Facio. Sitio web: https://www.ucr.ac.cr/ Teléfono: (506) 2511-4000. Correo de soporte: revistas@ucr.ac.cr, 2005)
The following article examinesthe application of the notions of fragmentation to the novel Picturing Will written by Ann Beattie. Fragmentation of style in this novel serves as strategy to support Beattie’s thematic development. Its employmentseemsto suggest that totalitarian and hegemonic viewsto importantsocial institutionssuch as marriage, parenthood, and family ought to be broken to open different possibilities of new forms ofrelating within them.At the same time, its employment also servesto disrupt the traditional literary conventions of crafting stories. Key words: fragmentation, photography, frames, angles, close-ups, long-shot, lightening.